Dinamika Sosial-Ekologis dan Tantangan Pembangunan di Kawasan Pesisir Terdegradasi: Kajian Kasus di Teluk Jakarta - Jelibseda, Jelibseda; Umar, Genius (Trends in Applied Sciences, Social Science, and Education, 2025)
Coastal and participatory development is a challenge as well as an opportunity for local governments in realizing the welfare of coastal communities without ignoring environmental sustainability. This study discusses various strategies carried out by local governments in encouraging coastal development that is oriented towards and involving the community. Through a multidimensional approach that includes social, economic, and environmental aspects, local governments are expected to be able to integrate policies that are responsive to the needs of the community and the ecological conditions of coastal areas. Strategies such as strengthening local institutions, increasing community capacity, and actively involving stakeholders are the main keys to creating inclusive development. In addition, the importance of socialization, wise management of natural resources, and cross-sector collaboration also support the achievement of development goals.